2008
DOI: 10.1007/s00420-007-0279-8
|View full text |Cite
|
Sign up to set email alerts
|

Playing-related disabling musculoskeletal disorders in young and adult classical piano students

Abstract: Our study showed MSDs to be a common problem among classical piano students. With variance in several studies reported, older students appeared to be more frequently affected by disabling MSDs and no difference in the prevalence rate of the disorders was found in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 16 publications
(23 reference statements)
0
42
0
2
Order By: Relevance
“…It has been viewed from various perspectives including strategies and approaches, daily practice (Hultberg 2008;Jorgensen and Hallam 2009), individual characteristics and conceptions (Gaunt 2010;MacNamara, Holmes, and Collins 2008), health problems (Bruno, Lorusso, and L'Abbate 2008;Kreutz, Ginsborg, and Williamon 2009;Phillips, Henrich, and Mace 2010), memorisation (Chaffin et al 2010;Ginsborg 2002) and motivation (McPherson 2009). Within the musical domain, practice routines reveal forms of self-regulated learning and refer to the ways in which students acquire control over their own development.…”
Section: Introductionmentioning
confidence: 99%
“…It has been viewed from various perspectives including strategies and approaches, daily practice (Hultberg 2008;Jorgensen and Hallam 2009), individual characteristics and conceptions (Gaunt 2010;MacNamara, Holmes, and Collins 2008), health problems (Bruno, Lorusso, and L'Abbate 2008;Kreutz, Ginsborg, and Williamon 2009;Phillips, Henrich, and Mace 2010), memorisation (Chaffin et al 2010;Ginsborg 2002) and motivation (McPherson 2009). Within the musical domain, practice routines reveal forms of self-regulated learning and refer to the ways in which students acquire control over their own development.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that fatigue and spinal pain were the most common factors, whereas the forearm was identified as the most affected body part. Various studies have reported gender differences in musculoskeletal pain prevalence, proposing that women are more likely to experience significantly higher incidents of pain (29)(30)(31). However, in this study the number of women (60%) and men (65%) reporting musculoskeletal problems were evenly distributed with men experiencing a slightly higher incidence of issues.…”
Section: Discussionmentioning
confidence: 99%
“…Na przykład islandzcy badacze wykazali, że wśród badanych studentów kierunków muzycznych ponad połowa otrzymała jedynie niewielką edukację dotyczącą prewencji dolegliwości mięśnio-wo-szkieletowych związanych z grą na instrumencie lub nie otrzymała jej wcale [7]. Dodatkowo, oprócz oczywistych czynników ergonomicznych związanych z postawą i pracą ciała w trakcie gry na instrumencie, czynnikami sprzyjającymi rozwojowi dolegliwości mięśniowo-szkieletowych mogą być długie godziny pracy, zwłaszcza jeśli jest ona wykonywana bez przerw lub odpowiedniej rozgrzewki [7,25], przekonanie dotyczące tego, że ból związany z grą na instrumencie jest akceptowalnym i normalnym zjawiskiem, kiedy wykonuje się zawód muzyka, oraz reakcja na już pojawiające się objawy [26][27][28][29].…”
Section: Dolegliwości Mięśniowo-szkieletoweunclassified
“…Podobne wyniki uzyskiwano we wcześniejszych badaniach porównujących studentów z profesjonalistami [25,30]. Także przegląd badań uwzględniających tylko studentów lub tylko profesjonalistów sugeruje podobne rozpowszechnienie dolegliwości mięśniowo--szkieletowych zarówno wśród młodych muzyków [7,9], jak i zawodowych instrumentalistów [5,6,8,10].…”
Section: Dolegliwości Mięśniowo-szkieletoweunclassified